2016
DOI: 10.1002/2015ja021271
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Jupiter's aurora observed by Hisaki/EXCEED: 1. Observed characteristics of the auroral electron energies compared with observations performed using HST/STIS

Abstract: Temporal variation of Jupiter's northern aurora is detected using the Extreme Ultraviolet Spectroscope for Exospheric Dynamics (EXCEED) on board JAXA's Earth‐orbiting planetary space telescope Hisaki. The wavelength coverage of EXCEED includes the H2 Lyman and Werner bands at 80–148 nm from the entire northern polar region. The prominent periodic modulation of the observed emission corresponds to the rotation of Jupiter's main auroral oval through the aperture, with additional superposed −50%–100% temporal var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…The unabsorbed power estimation for the Hisaki data is established by Tao et al . [, ]. See these references for the details for the estimation.…”
Section: Resultsmentioning
confidence: 99%
“…The unabsorbed power estimation for the Hisaki data is established by Tao et al . [, ]. See these references for the details for the estimation.…”
Section: Resultsmentioning
confidence: 99%
“…We used the model developed by Tao et al (, ) to convert the emission power in the 900–1,480 Å range to the corresponding unabsorbed total emission power from the northern hemisphere in the 700–1,800 Å UV range. This removes the effects of Jupiter's atmospheric absorption and rotational modulation from the data (see Tao et al, , , for details). Based on the unabsorbed power, we found that the identified 23 transient auroral events emitted energy of ~10 15 to 10 17 J/event, which corresponds to total electron energy of ~10 16 to 10 18 J/event precipitating into the auroral region.…”
Section: Discussionmentioning
confidence: 99%
“…The transient aurora with a peak power of ~2 TW, which is the strongest auroral power in the present analysis period, occurs during the interplanetary shock arrival at Jupiter on DOY 87. The unabsorbed emission power of the peak is estimated to be ~10 TW by the Tao et al (, ) model. The temporal intervals between the strongest event and adjacent transient auroras are ~10 days, which are longer than the most frequent interval of 2–6 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference of the power by a factor of ~8 is contributed by different estimation methods. The different wavelength range (Hisaki EXCEED: 900–1,480 Å, Juno UVS: 700–1,190 Å, and 1,230–1,620 Å) and exclusion of the auroral emission at the geocoronal emission lines for Hisaki EXCEED contributed to the difference by a factor of 3 when the color ratio of Hisaki EXCEED (Tao et al, ; Tao et al, ; Tao et al, ) was 1.5–2 corresponding to the time interval of our interest. In addition, the longitudinal modulation correction causes the difference by a factor of 2, since Juno UVS refers to the maximum intensity of the total power, whereas Hisaki EXCEED refers to the average of the total power.…”
Section: Instruments and Data Analysismentioning
confidence: 91%